2002
DOI: 10.1007/s00228-002-0444-7
|View full text |Cite
|
Sign up to set email alerts
|

Dosage form-related food interaction observed in a marketed once-daily nifedipine formulation after a high-fat American breakfast

Abstract: Under fasting conditions the modified-release characteristics of the test product are less pronounced than the reference product. No relevant impact of food intake could be observed for the reference product when switching from fasted to fed state, whereas a significant loss of modified-release characteristics could be detected for the test product under fed conditions resulting in much higher maximum concentrations. Such a phenomenon has been described in literature as "dose-dumping effect".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 7 publications
1
31
1
Order By: Relevance
“…Food co-administration with the »erosive tablet« caused much faster drug release, described as a »dose dumping« phenomenon (14). Similar results were obtained for the nifedipine extended release formulation containing encapsulated HPMC-based mini tablets, where »a significant loss of modified-release characteristics« was detected under fed conditions (29). In a separate study, it was found that food caused a pronounced delay in nifedipine absorption from Slofedipine ® XL, an enteric coated modified release tablet with erosive polymer matrix (30).…”
Section: The Extent Of Food Effectsupporting
confidence: 68%
See 1 more Smart Citation
“…Food co-administration with the »erosive tablet« caused much faster drug release, described as a »dose dumping« phenomenon (14). Similar results were obtained for the nifedipine extended release formulation containing encapsulated HPMC-based mini tablets, where »a significant loss of modified-release characteristics« was detected under fed conditions (29). In a separate study, it was found that food caused a pronounced delay in nifedipine absorption from Slofedipine ® XL, an enteric coated modified release tablet with erosive polymer matrix (30).…”
Section: The Extent Of Food Effectsupporting
confidence: 68%
“…In further investigations, hydrodynamic mechanical stress was considered to be the main factor responsible for postprandial effects on tablet erosion (10). Schug et al (14,29,30) reported formulationspecific food effects for different nifedipine modified release preparations. In vivo drug delivery profiles obtained by numerical deconvolution using p.o.…”
Section: The Extent Of Food Effectmentioning
confidence: 99%
“…Formulations utilizing capsules containing mini tablets,20 an eroding matrix,21 and a monolayer matrix22 all exhibited similar discrepancies when compared to nifedipine GITS. In all cases, this was characterized by inconsistent in vitro release properties at different pH values and a failure to demonstrate pharmacokinetic bioequivalence to nifedipine GITS.…”
Section: Comparisons Of Different Drugs and Formulationsmentioning
confidence: 98%
“…These have employed erosive tablet technology,19 a capsule containing several mini tablets,20 hydrophilic matrix tablets,21 a monolithic enteric-coated-like tablet with an erosive polymer matrix,22 an eroding matrix,23 and a monolayer matrix 24…”
Section: Other Once-daily Formulationsmentioning
confidence: 99%
See 1 more Smart Citation